Workers' sons rescue genetic diversity at the sex locus in an invasive honey bee population. Issue 7 (13th April 2019) - Gloag, Rosalyn S.; Christie, Joshua R.; Ding, Guiling; Stephens, Ruby E.; Buchmann, Gabriele; Oldroyd, Benjamin P.
Abstract: The hallmark of eusociality is the division of labour between reproductive (queen) and nonreproductive (worker) females. Yet in many eusocial insects, workers retain the ability to produce haploid male offspring from unfertilized eggs. The reproductive potential of workers has well‐documented consequences for the structure and function of insect colonies, but its implications at the population level are less often considered. We show that worker reproduction in honey bees can have an important role in maintaining genetic diversity at the sex locus in invasive populations. The honey bee sex locus is homozygous‐lethal, and, all else being equal, a higher allele number in the population lead to higher mean brood survival. In an invasive population of the honey bee Apis cerana in Australia, workers contribute significantly to male production: 38% of male‐producing colonies are queenless, and these contribute one‐third of all males at mating congregations. Using a model, we show that such male production by queenless workers will increase the number of sex alleles retained in nascent invasive populations following founder events, relative to a scenario in which only queens reproduce. We conclude that by rescuing sex locus diversity that would otherwise be lost, workers' sons help honey bee populations to minimize the negative effects of inbreeding after founder events and so contribute to their success as invaders.